A Multistrain Cluster of Methicillin-Resistant Staphylococcus aureus Based in a Native Community - Geoffrey Taylor; Terri Kirkland; Kinga Kowalewska-Grochowska; Ying Wang (Canadian Journal of Infectious Diseases)
Since 1986 the authors’ hospital has experienced increased numbers of methicillin-resistant Staphylococcus aureus (MRSA) isolates linked to residents of a native Indian community infected or colonized on admission. A survey of 422 consecutive persons from that community admitted to hospital over a three year period identified 21 (4.9%) carrying MRSA. In a case control study of 34 carriers compared to noncarriers from the community, only prior hospitalization within the past 12 months was identified as being significantly associated with the carrier state, but a specific hospital associated with this risk was not identified. A study of subsets of MRSA isolates in these patients revealed multiple strains present, identified by antibiograms, phage typing profiles and plasmid analysis. Community-based clusters of MRSA have only rarely been previously identified.